Intraocular pressure and ocular perfusion during hemodialysis - Barbosa,Carolina Pelegrini (2011)
AIM: To evaluate the intraocular pressure and ocular perfusion pressure during a hemodialysis. METHODS: Sixty-seven eyes from thirty-five patients were evaluated at the beggining of hemodialysis, 2 hours and 4 hours after initiation. Intraocular pressure was evaluated using a Tonopen. Systolic and diastolic arterial pressures were measured with a manual sphygmomanometer. The ocular perfusion pressure was estimated by mea suring the difference between 2/3 of the mean arterial pressure and the intraocular pressure values. Generalized estimating equations were used to evaluate the difference between the repeated measurements using the appropriate correction for inter-eye dependency. RESULTS: There was no statistically significant difference in ocular perfusion pressure, in intraocular pressure (p=0.93) and in systolic arterial pressure (p=0.92) at the three time points (p=0.69). But, when analyzing the extreme values, some patients exhibited lower diastolic perfusion pressures at all time points. CONCLUSION: Our results did not support the view that significant changes in ocular perfusion pressure and intraocular pressure occur during hemodialysis session. However, we observed that some patients exhibited lower diastolic perfusion pressures, which could be a poor prognostic factor for glaucoma patients.